Tackling fraud effectively in central government departments: A review of the legal powers, skills and regulatory environment of UK central government counter fraud teams. Issue 2 (8th May 2018) - Gilbert, Michael; Wakefield, Alison
Abstract : Purpose: Fraud has a significant effect on society. It has been estimated to cost the UK economy more than £50bn annually. The Government have signalled their determination to tackle these losses through a range of preventative, enforcement and collaborative activities. Diminishing police resources allocated to fraud means that this activity will need to be delivered by both law enforcement and civilian counter fraud teams. This paper aims to establish whether UK central government organisations have the legal powers, skills and regulation needed to tackle fraud effectively. Design/methodology/approach: This research was based upon a literature review, which included academic and other material, a semi-structured interview programme and a survey of counter fraud champions. Findings: Empirical data suggested that the effectiveness of central government civilian counter fraud teams is hampered by a fragmented legal landscape and a lack of skills, and that further professionalisation and regulation is needed to protect professional standards and individual legal rights. Research limitations/implications: Postal survey had 50 per cent response rate – below gold standard of 70 per cent. Practical implications: There are no practical implications, as this is a topical research area which is intended to inform counter fraud practice and development. Social implications: This research highlights limitations on the UK central government's ability to tackle fraud. There is therefore a low risk that, when published, this research could inform those considering fraudulent actions. Originality/value: This research was undertaken for a professional doctorate and has been sent to the Cabinet Office to inform their professionalisation programme. It filled a potential gap in the academic literature by looking at the perceived powers, skills and regulatory pressures in place within the UK central government and the extent of the current gap between current practice and the delivery of a fully professionalised service.